Vernonia amygdalina: a comprehensive review of the nutritional makeup, traditional medicinal use, and pharmacology of isolated phytochemicals and compounds - Degu, Sileshi; Meresa, Asfaw; Animaw, Zelalem; Jegnie, Mihretu; Asfaw, Asaye; Tegegn, Getachew (Frontiers in Natural Products, 2024)
Vernonia amygdalina is a perennial shrub that belongs to the family Asteraceae. The herb is an indigenous African plant that grows in most parts of sub-Saharan Africa. It is probably the most used medicinal plant in the genus Vernonia. Previous studies on the traditional medicinal value, nutritional composition, classes of phytochemical or compound isolation, and evaluation of their pharmacology activity are numerous. This provokes us to review and provide up-to-date evidence-based information on the study plant. A systematic online search using the databases of Google Scholar, PubMed, Science Direct, Wiley, Elsevier and Sci-Hub was carefully applied, using some important key words to get appropriate information. The leafy part of Vernonia amygdalina contributes greatly to the nutritional requirements for human health and to food security since it contains enough concentrations of proximate composition, minerals, and vitamins. The plant parts are used in traditional medicine for many human and animal health care purposes, including diarrhea, diabetes, wound healing, tonsillitis, evil eye, retained placenta, headache, eye disease, intestinal parasite, bloating, hepatitis, toothache, anthrax, malaria, urine retention, gastritis, stomach disorders, and snake bites. The chemical analysis revealed the presence of flavonoids, alkaloids, saponins, tannins, triterpenoids, sesquiterpene lactones, steroids, cardiac glycosides, oxalates, phytates, cyanogenic glycosides, phenols, and phenols. Additionally, various compounds such as vernolide, luteolin, vernodalol, vernoamyoside A, vernoamyoside B, isorhamnetin, glucuronolactone, and 1-Heneicosenol O-β-D-glucopyranoside were isolated. Some of the isolated compounds pharmacological activity was evaluated against some diseases and showed antioxidant, antibacterial, antifungal, antihelmintic, anticancer, and antiinflammatory potencies. Thus, the review provides comprehensive information about ethnomedicinal value, nutritional composition, isolated classes of phytochemicals, and compounds, including an evaluation of the pharmacological activity of the isolated compounds of Vernonia amygdalina. A review with this much information could be extremely valuable for future research on developing innovative nutraceutical products.